Deglacial Warming and Hydroclimate Variability in the Central Indonesian Archipelago. Issue 9 (19th September 2018) - Schröder, Jan F.; Kuhnt, Wolfgang; Holbourn, Ann; Beil, Sebastian; Zhang, Peng; Hendrizan, Marfasran; Xu, Jian
Abstract: We present centennial‐scale records of sea surface temperature and oxygen isotopes from the Celebes Sea, Makassar Strait, Flores Sea, and northwestern Banda Sea, which provide new insights into the variability of Indonesian hydroclimate over the past 25 kyr. Deglacial warming was generally gradual with an amplitude of 3–4 °C. Statistical evaluation of the temperature data suggests that the onset of deglacial sea surface temperatures warming in the tropical Indonesian Sea occurred earlier than the global atmospheric CO2 rise. In contrast to previous terrestrial precipitation records, our ice volume‐corrected δ 18 O of seawater (δ 18 Osw ) does not support widespread aridity in central Indonesia during the last glacial period. While δ 18 Osw was substantially enriched during Heinrich Stadial 1 and the Younger Dryas, δ 18 Osw values were only ~0.2‰ heavier during the Last Glacial Maximum than during the Holocene. Heavier δ 18 Osw during Heinrich Stadial 1 and the Younger Dryas either reflects a decline in precipitation amount and/or increased δ 18 O of rainfall in central Indonesia, both likely caused by a southward displacement of the tropical rain belt. Comparison of the Celebes Sea, Makassar Strait, Flores Sea, and Banda Sea records suggests that rainfall isotope and/or amount changes were comparable over Borneo and Sulawesi during the last termination. Key Points: Deglacial warming in the central Indonesian Archipelago started before 18 ka δ 18 Osw records do not support widespread aridity in central Indonesia during the last glacial period Heavier δ 18 Osw during stadials either reflect a decline in precipitation amount and/or increased δ 18 O of rainfall in central Indonesia